China in Central Asia: The Beginning of the End for Russia? - Garret Mitchell (Slovo, 2014)
With China continuing to make economic forays into Central Asia, attention has simultaneously turned toRussia’s privileged position in the region. A cursory glance through many articles concerned with the ‘Russia- Central Asia - China’ dynamic provides a misleading impression that Beijing’s strengthened ties with thecountries of Central Asia are coming at the expense of Moscow’s influence. This paper will show thatevents, conventionally characterized as breakthroughs in the ‘China - Central Asia’ relationship in the lastfour to five years, are in fact part and parcel of larger economic trends that began long before the inking ofthe energy and trade deals. The reality of China’s growing economic influence in Central Asia is notdisputed. What this paper will argue is that despite the heralded dislodging of Russia by China, Russia willcontinue to play a substantial role in the region through a combination of energy, culture, and military bondsthat run much too deep for Beijing to sever in the short to medium term. Click Here to read the article